In vivo response of GsdmA3Dfl/+ mice to topically applied fish oil – effects on cellular markers and macrophages. Issue 8 (12th July 2016) - Zulfakar, Mohd Hanif; Porter, Rebecca M.; Heard, Charles M.
Abstract : Psoriasis is an incurable autoimmune disease characterized by patches of abnormal red, itchy and scaly skin. This work examined the modulation of inflammation, hyperproliferation and immune cell markers following topical application of fish oil (FO) in comparison to the antipsoriatic agents, betamethasone dipropionate (BD) and salicylic acid (SA), to GsdmA3 Dfl /+ mice, a hair loss mutant which also exhibits epidermal hyperproliferation akin to psoriasis. The mice were dosed with 100 mg of the test formulation and after 10 days, the mice were sacrificed, skin sections excised and subjected to immunohistochemical determination of COX‐2, K17 and MAC‐1; and immunofluorescence of Ki‐67. Unchanged expression of the proinflammatory enzyme COX‐2 was observed in all treatments, suggesting the noninvolvement of COX‐2 in the aetiology of cutaneous aberration seen in GsdmA3 Dfl /+ mice. Intense staining of K17 and MAC‐1 in the FO‐treated group mirrored the epidermal thickening seen observed in live mice by optical coherence tomography (OCT). The ratio of Ki‐67‐positive nuclei per 100 basal cells indicated that hyperproliferation of keratinocytes occurred in FO‐treated mice and the opposite was true for BD‐treated mice. There was a positive correlation ( R 2 0.995) between Ki‐67 and the epidermal thickness data observed previously. In all immunochemical procedures, the combined BD, SA and FO formulation did not show any significant difference with the control group, reflecting observations seen previously. In conclusion, the epidermal changes observed following topical FO treatment on GsdmA3 Dfl /+ mice involves an increase in cellular proliferation and macrophages, although COX‐2 does not appear to play an important role. Abstract : This work examined the modulation of inflammation, hyperproliferation and immune cell markers following topical application of fish oil in comparison to the antipsoriatic agents, betamethasone dipropionate and salicylic acid, to GsdmA3 Dfl /+ mice, which exhibits epidermal hyperproliferation akin to psoriasis. The epidermal changes observed with the fish oil treatment correlated with the increased expression of the hyperproliferation markers, Ki67 and K17, but levels of the inflammatory marker COX‐2 were unchanged.